COACHING CLINIC PENGEMBANGAN KAPASITAS KETUA RT/RW DAN PENGURUS LPM KELURAHAN WALANTAKA KOTA SERANG - Titi Stiawati; Arenawati Arenawati; Andriyana Andriyana; Anas Anas; Muhamad Luay; Novan Hermawan (SEBA: Jurnal Pengabdian kepada Masyarakat, 2025)
The problem faced by the Walantaka Village Government is the lack of support from village community institutions, especially RT/RW in the field of administrative services and LPM (Community Empowerment Institution) in the field of village community empowerment. The purpose of this PKM is to provide training to be able to collaborate with stakeholders. The classical method used is that the RT head, RW head and LPM administrators of Walantaka Village are gathered in the village office hall with 2 training sessions. The first session before the material is delivered, a pre-test is held to measure the extent of understanding of the RT/RW heads and LPM administrators. The session is given practice on how to fill out the administration book that must be in the RT/RW administrators and in the LPM administration and is given games that can build effective communication. This second session ends with a Post Test, to measure the extent of acceptance of the RT/RW heads and LPM administrators regarding the material and practices that have been given. To realize the welfare of the community in the sub-district area, of course it cannot be implemented by the Lurah and his sub-district apparatus alone, but it requires support from the sub-district community institutions as partners at the sub-district level. In orderly administrative services, for example, support is needed from the RT head and RW head in helping to provide the required data. If the RT head and RW head cannot help optimally because they do not know what their main duties and functions are, then it is certain that the services provided by the sub-district will not be orderly in administration. Conclusion This coaching clinic activity increases the understanding and capacity of the RT/RW heads and LPM administrators in Walantaka Sub-district in carrying out their functions and roles in the community. Through this coaching, participants gain new insights regarding village-level governance.Keywood : Coaching Clinic, Service, Administrative Order